La coelio-appendicectomie, ce n’est pas pareil que l’appendicectomie conventionnelle: c’est mieux et ce doit être beaucoup mieux. Ou comment réduire le taux des abcès abdominaux secondaires? - Mouret, Ph. (2008)
The realisation today of simple appendicitis and complicated tre atement could not be done without the use of coelioscopy. However some authors are satisfied with rates of 1 to 2% of intra – abdominal sego n d a ry abcesses. The authors think that this rate can only be re l ated to an insufficient training or a bad use of the technique. Many experts have got rates much lower around 0.1-0.2%. These good outcomes are due to an extreme rigour carrying out three potentially iat rogenic stages: a perfect parietal and appendicular meso hemostasis, a perfect closure and condition of the stump, a systematic careful rinsing by washing- aspiration of Douglas pouch, a right iliac fossa and extraction port. To rea+ch this result, a washing- aspirating device is vital. The authors recommend, as often as possibl e, the coelio-assisted procedures "extra – abdominal" and "mixed", fast, sure and inexpensive and giving a lower rate of secondary abcesses, to be compared concerning safety but not costs with systematic use of endo-stapling. Keywords: Appendicitis, Coelio-appendicectomy, Laparoscopic appendicectomy, postoperat ive intra – abdominal abcesses.)